Model Pembelajaran Syariah di Jurusan Akuntansi - Krisno Septyan; Wisnu Julianto (Faculty of Economics, State University of Jakarta., 2018)
This research is aim to propose practically in Islamic accounting teaching to input fiqih muamalah and accountig are balanced. This research method is used critical Islamic accounting teaching based on prime of law source of Islam. This research shows that students and graduates have risks if department of accounting has no teach fiqih muamalah and department of acccounting will be achieved learning outcome for students and graduates if fiqih muamalah became part of teaching in Islamic accounting. We offer several ways to apply fiqih muamalah be a part in Islamic accounting teaching are (1) fiqih and accounting should be balance, (2) make two course accounting teaching like as intermediate accounting (Islamic accounting part 1 and part 2), (3) removing similliar discussion in Islamic accounting with financial accounting and (4) lecture make a literature about fiqih muamalah for student to independently studying. Keywords: Fiqih muamalah; Islamic accounting; Teaching